Uso de biomassa de bioflocos úmida e seca na alimentação da tilápia do Nilo - Caldini, Nayara Nunes (2015)
This study consisted of two complete and following experiments. In the first one, the objective was to demonstrate the technical feasibility of the separate BFT (bioflocs) tank technology in juvenile cultivation of Nile tilapia, for monitoring variables of water quality and productive performance. Fish were fed on different combinations of artificial food (balanced diet) and natural food (bioflocs biomass). As the supply of artificial food decreased, the biomass supply of bioflocs increased. Bioflocs biomass was produced in one external 500-L tank, separately from the cultivation system (separate tank BFT). The tanks which received daily applications of bioflocs showed significantly lower nitrite concentrations than those observed in tanks in which the only source of fish feed was a commercial feed. It was concluded that it can be reduced the regular feeding rates of juvenile Nile tilapia, with artificial diets, by 25 %, without losses, if bioflocs is provided as a food supplement in equal proportion. The second experiment has aimed determine the effects of the provision of dried bioflocs biomass to Nile tilapia juveniles, stocked in experimental rearing tanks for 8 weeks, upon selected variables of water quality, growth performance and effluents quality. Fish was fed with different combinations of artificial diets and bioflocs biomass in the wet (in natura) and dried form. As the supply of artificial diet was decreased, the provision of bioflocs biomass was increased in the same proportion. The bioflocs biomass was produced in two extra 500-L tanks. The growth performance of fish that were partially fed with dried bioflocs biomass has remained below what was observed in the tanks supplied with the wet bioflocs biomass. Due to the lacking of positive results, there is not any rationale to dry the bacterial bioflocs aiming at their delivery to the cultured fish.